Extraction and applications of Rayleigh wave ellipticity in polar regions - Glenn Jones (Annals of Glaciology, 2023)
Seismic Rayleigh wave ellipticity measurements are the horizontal-to-vertical ratio of the Rayleigh wave particle motion, and are sensitive to the subsurface structure beneath a seismic station. H/V ratios measured from the ambient vibrations of the Earth are being increasingly used in glaciological applications to determine glacier and ice sheet thickness, seismic velocities and firn properties. Using the newly developed degree-of-polarisation (DOP-E) method which exploits the polarisation properties of seismic noise, we identify and extract Rayleigh waves from seismic stations in Greenland, and relate them to sea ice processes and the geology of the upper crust. Finally, we provide some suggestions for future applications of DOP-E method to gain greater insight into seasonal and long-term variability of sea ice formation and breakup as well as the monitoring of ice sheet thickness, subglacial environment and firn layers in the poles.